Language as cultural practice : Mexicanos en el norte - Schecter, Sandra R. (L. Erlbaum Associates, Publishers, 2002)
This is an ethnographic account of language socialization practices within Mexican-background families in California and Texas. It illustrates cases where language is used by speakers to choose between self-definitions and where language interacts differentially with other defining categories.